Workshops and data collection: Ways to embed clinical complexity in learning events - Anna Treloar; Penelope Little; Teresa Stone; Margaret McMillan (Halla Newcastle Education and Research Center, 2017)
Objectives i) To explicate the constructivist nature of workshop processes to assist participants in the development of stories that are meaningful for educational purposes; ii) to position problem/practice-based learning (PBL) activities within constructivist theory. iii) to explore the construction and potential value of clinical anecdotes told by nurses to others new to the discipline of mental health nursing. Methods Three workshops were held, both to collect stories, and to record insights from two groups of experienced mental health nurses, and one group of undergraduates close to registration, about how the stories could be interpreted and the purpose of telling selected stories to newcomers to the discipline. Case study methodology was used for exploration of these stories because this is a flexible approach often used in educational research. It is particularly suitable where the question is "how?" or "why?" and the components of a case study are people, things, events, contexts and relationships, components which are suitable for analysis of stories about mental health nursing. Results Stories (n=100) were collected directly from mental health nurses during and after the workshops as well as a few previously published sources; these were analysed for their fitness for educational purposes. The stories fell into three main groups, the first at the surface level, dealing with the history of mental health nursing and providing examples of mental health nurse humour; the middle level offering a variety of insights into daily work in mental health nursing whether in the hospital, the community, the prison or other setting, and the deepest level stories showed the attitudes and skills developed by experienced mental health nurses. Conclusion Thoughtful structuring and facilitation of the workshops was critical to the data collection process. The clinical anecdotes collected capture much which is not contained in textbooks and those depicting deeper appreciation of the specialty, better equip students to enter the real world of mental health nursing, where not everything is predictable and orderly, and where "inspired creativity" is often required and shown to manage difficult situations. The analysis of storylines demonstrates that the manner in which one conceptualizes practice has the potential to impact on learning outcomes for a new generation of mental health nurses who work in novel contexts of practice.